Equipment and methods for hybrid technologies of ion beam and plasma surface materials modification; 9th International Conference on Modification of Materials with Particle Beams and Plasma Flows, Tomsk, 21-21September 2008 - Ryabchikov A. I. Aleksandr Ilyich
A new-generation installation for realization of hybrid technologies of the ion beam and plasma material treatment includes vacuum-arc generators of gaseous and metal plasma with the devices for micro-particles filtering, medium frequency dual magnetron, high current ion and plasma source, high voltage generator for high-frequency short-pulsed plasma-immersion ion implantation or coating deposition. With the use of the complex installation equipment an intermetallic Al → Ti system was formed in a target surface layer to a depth of 2600 nm with dopants concentration up to 60%. The abilities of improvement of the main physical and mechanical characteristics of coatings in comparison with conventional PVD technologies have been demonstrated on the example of formation of monolayer TiSiB coating and multilayer TiAlN/TiN coatings with the thickness of each separate layer varied from 2 to 10 nm.